Helicopter Vibratory Loads Alleviation through Combined Action of Trailing-Edge Flap and Variable-Stiffness Devices. (4th June 2015) - Gennaretti, Massimo; Bernardini, Giovanni; Serafini, Jacopo; Molica Colella, Marco
Abstract : The aim of this paper is the assessment of the capability of controllers based on the combined actuation of flaps and variable-stiffness devices to alleviate helicopter main rotor vibratory hub loads. Trailing-edge flaps are positioned at the rotor blade tip region, whereas variable-stiffness devices are located at the pitch link and at the blade root. Control laws are derived by an optimal control procedure based on the best trade-off between control effectiveness and control effort, under the constraint of satisfaction of the equations governing rotor blade aeroelastic response. The numerical investigation concerns the analysis of performance and robustness of the control techniques developed, through application to a four-bladed helicopter rotor in level flight. The identification of the most efficient control configuration is also attempted.